(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
COVID-19 was first reported in Wuhan, China on 17th November 2019 and since then it has affected 2,76,15,676 people worldwide, with 8,98,426 deaths.1 WHO declared COVID-19 as a public health emergency on 30th Jan 2020 and a global pandemic.2 Pakistan reported its first corona virus infected case on 26th Feb. 2020.3Since then the number of affected people in Pakistan increased exponentially reaching a figure of 2,98,509 confirmed cases on 5th September 2020.4